Is there a correlation between systolic heart failure and levels of toll-like receptor-5 and N-terminal pro-B-type natriuretic peptide? - Cetin Mirzaoglu; Tarik Kivrak; Mehmet Balin; Mehmet Ali Kobat; Orhan Dogdu; Ilgin Karaca (International Journal of the Cardiovascular Academy, 2018)
Objective: Specific biomarkers are essential in the diagnosis of heart failure. Our trial aim is determined that relationship between toll-like receptor-5 (TLR-5) and N-terminal pro-B-type natriuretic peptide (NT-ProBNP) in patients with reduced ejection fraction. Methods: Two groups were formed in our study (normal and patient group). Among the two groups were investigated that relationship between TLR-5 and NT-ProBNP. Results: The plasma levels of both NT-ProBNP and TLR-5 are significantly higher in patients with congestive heart failure than healthy individuals. However, there is no definite correlation between plasma levels of NT-ProBNP and TLR-5 in patients with congestive heart failure. The high-level plasma TLR-5 is of prognostic value independent from the plasma NT-ProBNP levels, in these patients. Conclusion: As a conclusion, according to recent studies, the high plasma levels of NT-ProBNP and TLR-5 are mainly associated with high mortality and longer hospitalization rate in individuals with heart failure. Therefore, the higher is plasma levels of markers such as TLR-5 and NT-ProBNP, the worse is the overall prognosis in these patients. NT- ProBNP and TLR-5 are thought to be the cheapest and the most appropriate marker to be determined.